Evaluating Public Service Quality Using the SERVQUAL Model: An Analysis of Key Service Dimensions - Garry Juadry Engko; Wahab Tuanaya; Normawati Normawati; Safrudin Bustam Layn (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2025)
This study assesses the quality of public services at the Benteng Village Office in Nusaniwe District, Ambon City, utilizing the SERVQUAL model across five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. While most indicators for Tangibles, Reliability, and Assurance are being met, there are notable gaps in the comfort of physical facilities and the technological proficiency of staff. The Responsiveness dimension aligns with community expectations; however, there are concerns regarding staff friendliness in the Empathy dimension. Key factors affecting service quality include the professionalism of human resources, IT infrastructure, and community oversight. The study recommends enhancing staff skills, upgrading facilities, and promoting a positive service culture to elevate service quality in Benteng Village.